A Study on High Efficiency Bidirectional LVDC for Vehicle ISG System - Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2026)
Background/Objectives: As recently, they have installed modules with various features related to the field of vehicles in the future, including hybrid vehicle and intelligent vehicle, it came to be difficult for the existing power supply to cover those sufficiently. In addition, judging from the recent intelligent keynote and hybrid development direction, a high-power converter becomes essential. Thus, research on the technology that achieves high efficiency is urgently needed.Methods/Statistical analysis: As recently, the need of high mileages of vehicle systems has come to the fore, studies for energy saving are actively conducted by applying the Idle Stop & Go (ISG) System technology that stops the engine running while idling. In general, the fuel consumed in the vehicle while idling takes up 5-8% of the total fuel consumption, so a Stop-Start System in the hybrid vehicle is considered one of the essential features.Findings: To maximize the efficiency of a Stop-Start system, it is essential to employ a maneuvering engine motor run at high voltage, and for this, it becomes generalized to build up a 48 [V] voltage system in the Stop-Start system. In the vehicle power system, for small capacity power, such as light and stereo systems, the existing 12 [V] voltage system is constructed, while in high-capacity systems such as start system, power steering, air conditioning and heating system, a binary system is applied, in which the 48 [V] voltage system is constructed, and in this binary system, the DC/DC converter for power supply between two power sources comes to have a four times higher boosting ratio. Because of this high boosting ratio, the non-isolated general DC/DC converter is not enough for the promotion of efficiency, so studies are conducted on various charging pumps for efficiency improvement. In this paper, propose a new topology and a construction method for 3kW class bidirectional DC / DC converters suitable for automotive systems with redundant power supplies. The proposed resonant charge pump uses input and output grounds in common, enables soft switching in a full load region, and has a very small inductor size.Improvements/Applications: In this paper, designed a controller of a DC/DC converter that could improve power quality and increase reliability, and as a result, the following conclusions could be drawn.
Keywords: ISG System(Idle Stop & Go system); Charge pump; High power converters; DC / DC converter; Hybrid vehicle